Figurative Language Found in Popular Songs of Secondhand Serenade - Hanggrai Diflas Diaga (PHILOSOPHICA Jurnal Bahasa, Sastra, dan Budaya, 2021)
This study focuses on figurative found in popular songs of Secondhand Serenade, they are "Broken", "A twist in my story" and "I hate this song". The data were taken from the three songs of Secondhand Serenade which consist of many types of figurative language by using Perrine’s (1992) theory. The descriptive method was applied in this research, the data source from the research is song lyrics from the three songs of Secondhand Serenade. The writer found 17 sentences containing figurative languages in Secondhand Serenade's songs. All of these terms are divided into six categories, They are, hyperbole, personification, metonymy, simile, apostrophe, and symbol. The writer more often found types of figurative language that contain hyperbole. Nine sentences are almost found in every song from the three songs of Secondhand Serenade. By reading this study, the writer hopes this research could give more understanding in the analysis of figurative language to the reader. The writer hopes this paper inspires all students who want to research in the same field. This study shows to the reader types of figurative language found in popular songs of Secondhand Serenade.